Ferrite content meter analysis for delta ferrite evaluation in superduplex stainless steel - Cesar G. Camerini; Vitor Manoel A. Silva; Iane A. Soares; Rafael Wagner F. Santos; Julio Endress Ramos; João Marcio C. Santos; Gabriela Ribeiro Pereira (Journal of Materials Research and Technology, 2018)
Superduplex stainless steel is a widely used material in many industrial areas, due to its significant properties in terms of mechanical and corrosion resistance. In order to guarantee the quality of these steels, the ferrite evaluation is an important analysis since many properties depend on the control of the ferrite content. During equipment manufacturing or field inspections, the most conventional way to evaluate the ferrite content is through ferritoscope measurements, due to its portability and easy interpretation. However, it has been observed that the calibration pattern used for ferritoscope calibration can lead to inaccurate ferrite quantification in superduplex inspection. In order to analyze this influence, different characterization techniques were performed in superduplex samples, such as optical microscopy, X-ray diffraction, and vibrating sample magnetometer, to compare with the measurements obtained by a ferritoscope. It was concluded that for high ferrite values, with the calibration made from the calibration pattern provided by the ferritoscope manufacturers, the ferrite values measured showed significant deviations from the real values. The current work presents a solution for using the ferritoscope for a more accurate quantification of the ferrite content in superduplex stainless steels. Keywords: Superduplex stainless steel, Ferrite content meter, Calibration procedures, X-ray diffraction